Robotic excavation in construction automation. - Quang Ha
This article presents some results of the autonomous excavation project conducted at the Australian Centre for Field Robotics (ACFR) with a focus on construction automation. The application of robotic technology and computer control is one key to construction industry automation. Excavation automation is a multidisciplinary task, encompassing a broad area of research and development. The ultimate goal of the ACFR excavation project is to demonstrate fully autonomous execution of excavation tasks in common construction, such as loading a truck or digging a trench. A number of difficult theoretical and practical problems must be solved to achieve this objective. The problems fall into three main groups: excavation planning, sensing and estimation, and control
Keywords: ACFR excavation project; Australian Centre for Field Robotics; Autonomous excavation project; Bucket-soil interactions; Computer control; Construction automation; Control strategies; Electrohydraulic systems; Estimation strategies; Excavation planning; Impedance control; Position/force control; Robotic excavation; Sensing; Trench digging; Truck loading; Variable-structure-based techniques